Estudo tribológico do revestimento de Stellite 6, Aspergido por HVOF antes e após polimento, e do substrato de aço inoxidável AISI 304 - (:unkn) unknown (Universidade Federal do Pampa, 2018)
With the increasing mechanical evolution, there has also been a need for continuous improvement of mechanical components. In this way, some problems are faced with a certain frequency, as an example we have the theme of this work, the wear of mechanical components caused by the interaction between different materials. With the need to obtain a surface that increases the useful life of parts and components of machines and which possesses mechanical properties that are resistant to the abrasive wear, a surface by thermal spraying was coated by the HVOF deposition method (High Velocity Oxygen Fuel) with a cobalt alloy, commercially known as Stellite 6. This coating, with a higher hardness than the substrate, is characterized by its high wear resistance, here emphasizing abrasion. It has a dense structure, with a low level of porosity and a good anchoring to the substrate. The coated samples were analyzed by Scanning Electron Microscopy (SEM) to verify and qualify coating quality, microhardness analysis, wear test and rough’ness test. The tests and analyzes showed that the Stellite 6 coated samples showed better performance in the microhardness, wear and roughness tests (if polished) compared to the AISI 304 stainless steel substrate samples.
Keywords: Engenharia mecânica; Desgaste abrasivo; Aspersão térmica; Revestimentos; Stellite 6; Mechanical engineering; Abrasive wear; Thermal spraying; Coating; CNPQ::ENGENHARIAS